Functional exosome-mimic for delivery of siRNA to cancer: in vitro and in vivo evaluation - Yang, Zhaogang; Xie, Jing; Zhu, Jing; Kang, Chen; Chiang, Chiling; Wang, Xinmei; Wang, Xiaobing; Kuang, Tairong; Chen, Feng; Chen, Zhou; Zhang, Aili; Yu, Bo; et al. (Journal of controlled release, 2016)
Exosomes, the smallest subgroup of extracellular vesicles, have been recognized as extracellular organelles that contain genetic and proteomic information for long distance intercellular communication. Exosome-based drug delivery is currently a subject of intensive research. Here, we report a novel strategy to produce nanoscale exosome-mimics (EMs) in sufficient quantity for gene delivery in cancer both in vitro and in vivo. Size-controllable EMs were generated at a high yield by serial extrusion of non-tumorigenic epithelial MCF-10A cells through filters with different pore sizes. siRNA was then encapsulated into the EMs by electroporation. Biosafety and uptake efficiency of the EMs were evaluated both in vitro and in vivo. The mechanism underlying their cellular endocytosis was also studied. [Display omitted]